2013
DOI: 10.1902/jop.2012.120343
|View full text |Cite
|
Sign up to set email alerts
|

Doxycycline‐Loaded β‐Tricalcium Phosphate Release Following EDTA Root Surface Etching Improved the Clinical Outcomes in Chronic Periodontitis: An In Vivo Study

Abstract: EDTA root surface etching enhances DOX availability in the GCF following its release from β-TCP as a drug carrier.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 70 publications
(129 reference statements)
0
8
0
Order By: Relevance
“…Group 3 and group 4 reported significantly higher PPD reduction and CAL gain compared with group 1 and group 2 with no significant difference between them. This finding could be related to EDTA root surface etching for both groups that could enhance SMV availability with its subsequent more sustained effects on soft tissue parameters . This assumption was supported by crevicular fluid evaluation which revealed significantly higher SMV concentration in group 3 and group 4 compared with groups 1 and 2.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…Group 3 and group 4 reported significantly higher PPD reduction and CAL gain compared with group 1 and group 2 with no significant difference between them. This finding could be related to EDTA root surface etching for both groups that could enhance SMV availability with its subsequent more sustained effects on soft tissue parameters . This assumption was supported by crevicular fluid evaluation which revealed significantly higher SMV concentration in group 3 and group 4 compared with groups 1 and 2.…”
Section: Discussionmentioning
confidence: 57%
“…40,41 Many studies reported positive results during the regeneration of periodontal bone defects after the application of SMV with methylcellulose gel. 30,31,42,43 This non-significant difference in pocket reduction between the two groups also ensures the 22,23 This assumption was supported by crevicular fluid evaluation which revealed significantly higher SMV concentration in group 3 and group 4 compared with groups 1 and 2. The non-significant differences between the two groups could reflect a maximum stimulatory effect of SMV in augmenting soft tissue parameters.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…These factors can be attributed to the effects of DOX, such as inhibition of MMPs (collagenase and gelatinase) and implementation of a positive impact on the bone repair process. In addition, it provides anti-inflammatory effects by suppressing the number of polymorphonuclear leukocytes and blocking the release of prostaglandin E2 (31)(32)(33). Another important factor is the way DOX is used, since authors stated that DOX gel is able to remain in the subgingival site for a minimum period of ten days, and its mechanism of action thus reduced the volume of the gingival crevicular fluid (GCF) and the transforming growth factor beta 1 (TGF-ß1), with improved clinical signs of inflammation, decreased probe depth and clinical gain of insertion (34,35).…”
Section: Discussionmentioning
confidence: 99%